Cost-Sharing Requirements for the Herpes Zoster Vaccine in Adults Aged 60+. (December 2019) - Tak, Casey R.; Kim, Jaewhan; Gunning, Karen; Sherwin, Catherine M.; Nickman, Nancy A.; Biskupiak, Joseph E.
Background: Rates of zoster vaccination in US adults aged 60+ were approximately 30.6% in 2015. Out-of-pocket cost-sharing has been identified as a major barrier to vaccination for patients. To date, herpes zoster vaccine cost-sharing requirements for adults aged 60 to 64 has not been described.Objective: Compare the cost-sharing requirements for zoster vaccination in adults aged 60 to 64 and adults aged 65+.Methods : A retrospective cohort design examined pharmacy claims for zoster vaccination from the Utah All Payer Claims Database for adults aged 60+. Descriptive statistics and a 2-part cost model compared cost-sharing requirements for adults aged 60 to 64 and adults 65+.Results: Of the 30 293 zoster vaccine claims, 13 398 (45.8%) had no cost-sharing, 1716 (5.9%) had low cost-sharing (defined as 1 to less than 30), and 14 133 (48.3%) had high cost-sharing (defined as 30 or more). In the cost models, adults aged 65+ had higher odds of any cost-sharing (odds ratio = 39.86) and 29% higher cost-sharing as compared with adults aged 60 to 64.Conclusions : Adults aged 60 to 64 encounter lower cost-sharing requirements than adults aged 65+. Providers should be cognizant of this dynamic and encourage zoster vaccination prior to the age of 65.